Effect of downstream processing on the structure and rheological properties of xanthan gum generated by fermentation of Melaleuca alternifolia residue hydrolysate. (November 2022) - Li, Zhi-Xuan; Chen, Jia-Yu; Wu, Yi; Huang, Zhong-Ying; Wu, Shu-Ting; Chen, Yun; Gao, Jing; Hu, Yong; Huang, Chao
Abstract: Low-cost Melaleuca alternifolia residue hydrolysate has great potential as a promising substrate for xanthan gum production but further downstream processing in addition to traditional alcohol-precipitation is necessary to obtain purified xanthan gum from this substrate. In this study, the effect of downstream processing on the structure and rheological properties of xanthan gum generated by fermentation of Melaleuca alternifolia residue hydrolysate was evaluated for the first time. Compared with acid-precipitation and alkali-precipitation, dialysis was much more suitable for xanthan gum purification as demonstrated by the energy dispersive spectrometer (EDS) and thermogravimetric analysis (TGA) results, and the xanthan gum with relatively high purity could be obtained after alcohol-precipitation and dialysis. Dialysis after alcohol-precipitation showed little influence on the functional groups of xanthan gum but the microstructure of xanthan gum changed greatly in that a filamentous structure was formed after this treatment. The fermentation performance could be evaluated accurately based on the suitable downstream processing. The purified xanthan gum had similar rheological properties (pseudoplasticity and solid-like/gel-like behavior) to the typical xanthan gum according to its flow curves and linear viscoelastic analysis. However, some rheological properties (existence of Newtonian plateau in flow curves, and crossover of storage modulus (G′) and loss modulus (G″) in frequency sweep test) of the purified xanthan gum solution were different from that of the typical xanthan gum. Overall, this study can offer some important information for efficient and effective purification of xanthan gum with a good rheological performance from low-cost Melaleuca alternifolia residue hydrolysate. Graphical abstract: Image 1 Highlights: Effect of downstream processing on xanthan gum structure was evaluated. Effect of downstream processing on xanthan gum rheological properties was learned. Melaleuca alternifolia residue hydrolysate was suitable for xanthan gum production. Purified xanthan gum with good rheological performance was obtained.